APR Financial Stress Scale: Development and Validation of a Multidimensional Measurement - Wookjae Heo; Soo Hyun Cho; Philseok Lee (Journal of Financial Therapy, 2020)
People usually experience financial stress in managing their financial resources. Despite financial stress’s importance in life outcomes and the need for a comprehensive and theory-based measurement of the construct, few studies have addressed the conceptual issues of financial stress and its measurement. Hence, by borrowing from theories of general stress, this study attempts to fill this gap. Using an expert panel and two separate online survey samples, we developed and validated a novel financial stress scale. A total of 688 responses were used in an exploratory factor analysis and 1,115 responses were used in a confirmatory factor analysis. This multidimensional financial stress scale consists of 24 items and represents affective (A), physiological (P), and relational (R) aspects of financial stress. Researchers and practitioners can use this scale to understand the complex nature of financial stress and tailor their intervention efforts accordingly.
Keywords: Financial Stress; Scale Development; Measurement; Money Management; Stress